2013
DOI: 10.1590/s1516-05722013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Baccharis rufescens Spreng. var. tenuifolia (DC.) Baker: contribuição ao estudo farmacognóstico

Abstract: RESUMO:Baccharis rufescens Spreng. var. tenuifolia (DC.) Baker pertence à família Asteraceae e é usada na medicina tradicional como estomáquico e hepatoprotetor. Um estudo fitoquímico mostrou a presença de flavonoides e triterpenos, sendo que os extratos clorofórmico e metanólico de folhas apresentaram-se ativos no bioensaio de toxicidade sobre Artemia salina Leach. Além disso, extratos clorofórmicos evidenciaram a presença de peróxidos, sugerindo sua aplicação no tratamento da malária (Schenkel at al., 2002;M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…This type was common in Asteraceae family (Krak1 and Mráz 2008; Tavares et al 2012). Asteraceae typically exhibits a mesophyll differentiated into palisade and spongy parenchyma (Oliveira et al 2011;Souza et al 2011;Duarte et al 2011;Souza et al 2013). Calea serrata have shown an isobilateral arrangement for chlorenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…This type was common in Asteraceae family (Krak1 and Mráz 2008; Tavares et al 2012). Asteraceae typically exhibits a mesophyll differentiated into palisade and spongy parenchyma (Oliveira et al 2011;Souza et al 2011;Duarte et al 2011;Souza et al 2013). Calea serrata have shown an isobilateral arrangement for chlorenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, crystals were found in the leaves and stems. Crystals have been reported in the perimedullary region of stems in several Baccharis species (Budel & Duarte, 2008;Souza et al, 2011;Oliveira et al, 2011;Jasinski et al, 2014;Barreto et al, 2015;Bobek et al, 2015;Almeida et al, 2021). "…”
Section: Morphology and Distribution Of Crystalsmentioning
confidence: 98%
“…In Asteraceae, particularly in Baccharis L., the crystals are generically described as incidental observations and in situ analyzes of the chemical composition of crystals are scarce or absent (Budel et al, 2003;Budel et al, 2004;Souza et al, 2011;Santos et al, 2012). The genus comprises 442 species (Heiden & Bonifacino, 2021), is monophyletic (Heiden et al, 2019), and presents similarities in the morphological features among several groups of closely related species causing challenges in taxonomic studies of the group (Bobek et al, 2016;Budel et al, 2018;Almeida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Asteraceae, particularly in Baccharis L., the crystals are generically described as incidental observations and in situ; analyses of the chemical composition of crystals are scarce or absent (Budel et al, 2003;Budel et al, 2004;Santos et al, 2012;Souza et al, 2011).…”
mentioning
confidence: 99%